2001
DOI: 10.1001/archopht.119.8.1171
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Protein Kinase Inhibitor, HA1077, on Intraocular Pressure and Outflow Facility in Rabbit Eyes

Abstract: To elucidate the roles of protein kinase in regulating the intraocular pressure (IOP) and outflow facility in rabbit eyes. Materials and Methods: A protein kinase inhibitor, 1-(5-isoquinolinesulfonyl)-homopiperazine (HA1077), was used. The IOP and the outflow facility were measured before and after topical, intracameral, or intravitreal administration of HA1077 in rabbits. Western blot analysis was performed to detect the 20-kd light chain of myosin in human trabecular meshwork (TM) cells and bovine ciliary mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
118
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(131 citation statements)
references
References 42 publications
12
118
0
1
Order By: Relevance
“…3). The magnitude of this facility increase is comparable to the 80% facility increase observed in porcine eyes after 3 hrs perfusion (Rao et al, 2001), but was less than the 2-and 3-fold increase observed after 3 hrs in rabbits (Honjo et al, 2001) and after 60-90 min in monkeys (Tian et al, 2005), respectively. Perfusion with tracer microspheres did not appear to influence outflow facility compared to the value immediately prior to tracer perfusion (8 ± 7%, p = 0.31).…”
Section: Outflow Facilitysupporting
confidence: 68%
See 2 more Smart Citations
“…3). The magnitude of this facility increase is comparable to the 80% facility increase observed in porcine eyes after 3 hrs perfusion (Rao et al, 2001), but was less than the 2-and 3-fold increase observed after 3 hrs in rabbits (Honjo et al, 2001) and after 60-90 min in monkeys (Tian et al, 2005), respectively. Perfusion with tracer microspheres did not appear to influence outflow facility compared to the value immediately prior to tracer perfusion (8 ± 7%, p = 0.31).…”
Section: Outflow Facilitysupporting
confidence: 68%
“…In particular, such drugs include cytochalasin (Johnson, 1997;Kaufman and Erickson, 1982;Tian et al, 1999a), latrunculin (Ethier et al, 2006;Sabanay et al, 2006), H-7 (Bahler et al, 2004;Sabanay et al, 2004) and Y-27632 (Honjo et al, 2001;Rao et al, 2001;Tian and Kaufman, 2005;Waki, 2001), and are therefore important candidates for the next generation of glaucoma therapy. How these potential "glaucoma drugs" work to reduce outflow resistance, however, is much less understood, but determining their mechanism in the trabecular meshwork and their influence on aqueous outflow hydrodynamics is important for developing novel drugs that target specific sites of outflow limitation -namely, the inner wall endothelium of Schlemm's canal and the underlying juxtacanalicular connective tissue (JCT) (Maepea and Bill, 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences might be related to NOS isozymes expressed in different organs. Y27632 has been previously shown to have significant effects on morphology in rat astrocytes when used alone at lower concentrations than that used here (Honjo et al, 2001). However, no significant changes in morphology were observed after Y27632 treatment of mouse astrocytes in the current study.…”
Section: Discussionmentioning
confidence: 74%
“…ROCK inhibitors are the first class of glaucoma drugs to increase aqueous humor outflow by working directly on the TM and SC cells, thus lowering IOP. Different ROCK inhibitors (Y-27632, H-1152, and fasudil) have been shown to induce rapid and long-lasting lowering of IOP (within 30 min and lasting for 6-12 h) in various animal models, including rabbit and monkey (39)(40)(41) . The exact mechanism by which Rho inhibitors increase the outflow facility through the conventional pathway is not completely understood.…”
Section: Rock Inhibitorsmentioning
confidence: 99%